Transmission of SARS‑CoV‑2 in northern Ghana: insights from whole‑genome sequencing - Sylverken Angelina Augustina; El‑Duah Philip; Owusu-Dabo Ellis; Schneider Julia; Owusu Michael.. (SPRINGER, 2023)
This article is published by Springer and is also available at https://doi.org/10.1007/s00705-021-04986-3